2015
DOI: 10.3389/fbioe.2015.00124
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Fatigue and Psychophysiological Test Performance from Speech for Safety-Critical Environments

Abstract: Automatic systems for estimating operator fatigue have application in safety-critical environments. A system which could estimate level of fatigue from speech would have application in domains where operators engage in regular verbal communication as part of their duties. Previous studies on the prediction of fatigue from speech have been limited because of their reliance on subjective ratings and because they lack comparison to other methods for assessing fatigue. In this paper, we present an analysis of voic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 36 publications
(40 reference statements)
2
14
0
Order By: Relevance
“…In this paper, we develop and evaluate some neuralnetwork architectures for infant cry classification. In this we have built on our previous investigations into the classification of other paralinguistic properties of the voice: for Cognitive Load [3], for Fatigue [4], and for the Common Cold [5]. The strategy in these previous studies has been to create wellmotivated feature sets that capture temporal, spectral and modulational properties of each audio token relevant for the task, and then summarize those features over each token using a number of statistical functions.…”
Section: Taskmentioning
confidence: 99%
“…In this paper, we develop and evaluate some neuralnetwork architectures for infant cry classification. In this we have built on our previous investigations into the classification of other paralinguistic properties of the voice: for Cognitive Load [3], for Fatigue [4], and for the Common Cold [5]. The strategy in these previous studies has been to create wellmotivated feature sets that capture temporal, spectral and modulational properties of each audio token relevant for the task, and then summarize those features over each token using a number of statistical functions.…”
Section: Taskmentioning
confidence: 99%
“…More recent research has examined the potential of speech analysis to detect fatigue. The research has found a good association between voice production and measures of fatigue, and several studies [46][47][48] have suggested that the analysis of speech can offer a reliable, continuous and objective measure of fatigue. However, the quality of speech recognition is heavily dependent on ambient noise in the environment.…”
Section: Monitoringmentioning
confidence: 99%
“…Our previous computational paralinguistics studies have shown the importance of feature normalisation to aid learning [3,4]. Without normalisation, learning may be affected by large differences in dynamic range across features, poor distributional properties or outlier values.…”
Section: Normalisationmentioning
confidence: 99%
“…For studying the effect of fatigue on voice, Baykaner et al used a combination of time-domain, spectral domain and modulation domain features [4].…”
Section: Features For Detecting Health Changesmentioning
confidence: 99%
See 1 more Smart Citation